Strategi Orang Tua dalam Mengajar dan Mendidik Anak dalam Pembelajaran At The Home Masa Pandemi Covid-19 - Eva Luthfi Fakhru Ahsani (Al Athfal : Jurnal Kajian Perkembangan Anak dan Manajemen Pendidikan Usia Dini, 2020)
Learning at home makes the co-19 distribution chain break. In implementing the school from home system, parents are very important in the learning process of students during the online system in learning at the home today. So with the study at home, parents who become educators at home as a substitute for the teacher. This study aims to describe the strategies of parents in teaching and educating children in learning at the home in a co-19 pandemic. This research was conducted using qualitative methods by field research directly at home. The strategy of parents teaching and educating their children in learning at the home pandemic covid-19 by accompanying children to learn at home by understanding children's learning styles and preparing a comfortable children's learning environment so as to minimize the spread of Covid-19.